Hubungan Pengetahuan Ibu Dengan Status Gizi Pada Balita di Puskesmas Patinggalloang Kota Makassar - Rosdianah, Rosdianah; Asmirah, Rika; S, Irmawati (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
The nutritional status of toddlers is an important thing for parents to know. The impact of malnutrition on toddlers can have an impact on the growth and development of toddlers. The aim of this research is to determine the factors that influence the nutritional status of toddlers at the Patinggiloang Community Health Center, Makassar City.This research uses quantitative research with a cross-sectional study approach. Respondents in this study were 24 respondents, taken using purposive sampling technique. So the output uses Chi Square Tests, p value = 0.008 < 0.05 then Ho is rejected. So, it can be concluded that there is an influence of knowledge on the nutritional status of toddlers.It is necessary to increase the knowledge of parents, especially mothers, in preparing menus for toddlers so that their nutritional intake is appropriate and their nutritional status improves by following the counseling held at the nearest community health center/posyandu, such as counseling about balanced nutrition, appropriate food for toddlers, the impact of malnutrition on toddlers, the right way to cook for toddlers, etc